Affect of Information Systèmes on Employee Development within the Employees at the Housing and Utilities Projects Implementation Agency - Ajfara (Comprehensive Journal of Science, 2025)
: This study aims to analyze the impact of information systems on employee development within the General Projects Authority – Jafara Branch. The research explores the role of information systems in enhancing performance efficiency, developing skills, facilitating administrative communication, and supporting decision-making at various levels. The findings indicate that the effective use of information systems directly contributes to improving employee productivity by providing accurate data and technological tools that enable better task performance. Moreover, the study highlights that information systems foster a culture of continuous learning and professional development, which positively influences service quality and supports the achievement of the Authority’s objectives
Keywords: Information Systems ، Data ،Development، Technology، Skills